Optimalisasi Pengetahuan Masyarakat Tentang Penggunaan Obat Harian Secara Aman di Desa Candirejo Ungaran Barat - Dea Ayu Vidina; Ibnu Nugroho Saputra; Dimas Adam Asrori; Sikni Retno Karminingtyas (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
Irrational drug use remains a common health problem in the community, including the use of medications without following dosage instructions, discontinuation of treatment before completion, the use of antibiotics without prescriptions, and improper drug storage. These problems were also identified among residents of Candirejo Village, West Ungaran District, who still have limited knowledge regarding the safe use of daily medications. This community service activity aimed to improve public knowledge and awareness regarding rational and safe medication use. The implementation methods included program socialization, health education sessions, distribution of educational media in the form of leaflets and posters, and evaluation through question-and-answer sessions and simple quizzes. Educational materials covered how to read medication labels, proper dosage and duration of use, differences between over-the-counter drugs and prescription drugs, risks of antibiotic misuse, and proper medication storage methods. The results of the activity showed an increase in community understanding regarding medication use instructions, the importance of reading labels, the dangers of using antibiotics without prescriptions, and correct drug storage practices. Participants also demonstrated high enthusiasm and active participation during the activities. This program is expected to improve community health literacy and encourage more appropriate, safe, and responsible medication use behavior in daily life.